Socialization of the Love of Eating Fish at the Nurul Mu'minin TPA, Maros Regency - Muhammad Fuad; Kasman, Risqah Amaliah; Muhammad Fadli; Fahd Abdul Azis (Program Studi Manajemen FEB UNM, 2025)
The main focus of this activity is to provide education to students about the importance of consuming fish. The socialization activity at TPA Nurul Mu'minin began with a preparation stage in the form of a coordination visit to obtain permits and prepare facilities. The opening activity was carried out through the introduction of the implementing team, a speech from the head of TPA, and involved 50 students and teachers. The socialization material included an introduction to types of fish, their nutritional content, and the benefits of consuming fish for health, which were presented interactively using PowerPoint presentations and leaflets. Lead questions were used to encourage active participation from participants. After the material was delivered, a discussion and question and answer session took place, where participants enthusiastically asked questions, demonstrating a good understanding of the material presented.